Undergraduates Self-Regulated Learning: the Place of Social Media Addiction and Learning Strategies - Iyiola, Ebunoluwa T.; Azikiwe, Judith C.; Omolayo, Benjamin O. (Universitas Negeri Semarang, 2021)
The emergence and wrong use of social media coupled with the lack of initiative for an acceptable learning strategy are factors for poor academic performance. Self-regulated learning improves academic performance, but there is a paucity of research on social media addiction, learning strategies and self-regulated learning. This study examined the role of social media addiction and learning strategy in undergraduates' self-regulated learning. Three hundred and fifty (350) participants conveniently sampled across four (4) universities in Nigeria responded to a structured questionnaire consisting of scales measuring variables of interest. Using Analysis of Variance and Independent T-test analyses, results showed that learning strategy and social media addiction have significant influence on self-regulated learning while gender had no significant influence on self-regulated learning. It is therefore concluded that social media addiction and learning strategy are determinants of self-regulated learning, and impacts on the academic performance of undergraduate students. Abstrak Kehadiran dan kesalahan penggunaan media sosial ditambah kurangnya inisiatif untuk strategi pembelajaran yang dapat diterima adalah faktor-faktor penyebab buruknya capaian pembelajaran. Pembelajaran mandiri memang mampu meningkatkan capaian akademik, tetapi tidak banyak penelitian terkait dengan kecanduan media sosial, strategi pembelajaran, dan pembelajaran mandiri. Penelitian ini mengkaji peran kecanduan media sosial dan strategi belajar mandiri mahasiswa. Responden penelitian ini sebanyak tiga ratus lima puluh (350) dari empat (4) universitas di Nigeria, dan semuanya merespon kuesioner terstruktur yang berupa skala ukur terhadap variabal ketertarikan. Dengan menggunakan analisis varian dan independent T-test, penelitian ini menunjukkan bahwa strategi pembelajaran dan adiksi media sosial berpengaruh signifikan terhadap self-regulated learning, sedangkan gender tidak berpengaruh secara signifikan terhadap self-regulated learning. Oleh karena itu disimpulkan bahwa kecanduan media sosial dan strategi pembelajaran merupakan faktor penentu pembelajaran mandiri dan berdampak pada capaian pembelajaran mahasiswa.